Lyophyllum lixivium (Lyophyllaceae, Agaricales), a new species from Yunnan, China - Lyu, Tong; Tang, Song-Ming; He, Jun; Wang, Shuai; Wu, Xiao-Qu; Chen, De-Chao; Ao, Cheng-Ce; Li, Shu-Hong (Phytotaxa, 2024)
Lyophyllum lixivium sp. nov., collected from southwestern China, is described, illustrated, and discussed based on morphological characteristics and molecular data (ITS and nrLSU). Lyophyllum lixivium has umbonate to slightly depressed pileus, a cylindrical stipe that slightly enlarges towards the base, fuzz at the base, basidiospores mostly broadly ellipsoid, rarely fusiform lacrymoid or amygdaliform with an acute apex in side view, abundant clamp connections at the pileus surface and hymenophoral trama. Morphologically and phylogenetically similar species were compared with L. lixivium in this study.